Differences in Hadith Understanding about Rukyat Al-Hilal According to Nahdatul Ulama and Muhammadiyah - Ai Nurjanah; Adnan Adnan (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the differences in the understanding of hadith about rukyat between Nahdatul Ulama and Muhammadiyah organizations. This research is a qualitative type through literature study by applying the sharah hadith method and comparative analysis. The results and discussion of this study indicate that there are differences between Nahdatul Ulama and Muhamadiyah in determining the beginning of the month of Qomariah, especially Ramadhan, Syawal and Dzulhijah. Nahdatul Ulama uses rukyatul hilal and istikmal because in books that muktabar rukyatul hilal and istikmal have clear sanad and reckoning only as an assistant when in the field. Meanwhile, Muhamadiyah in determining the beginning of the month of Qomariah did not use the rukyatul hilal but instead used the true reckoning method with the criteria for the form of al-hilal, but the traditions about rukyat were still used. This research concludes that basically Nahdatul Ulama and Muhamadiyah have no fundamental differences where Muhammadiyah views that the urfi reckoning system has several weaknesses so that it is still consistent with the criteria of wujudul hilal and considers reckoning in modern times obligatory and non-negotiable, while Nahdatul Ulama tend to rely on salaf ulama based on a cautious attitude, even though they have made predictions, they will still wait for the results of rukyat in the field when determining the beginning of the month. In this case, Nahdatul Ulama and Muhammadiyah agree that rukyat and reckoning are the means to determine the beginning of entering the month of Qomariah today.